1978
DOI: 10.1093/clinchem/24.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of gamma-glutamyltransferase from human liver, and comparison with the enzyme from human kidney.

Abstract: We isolated gamma-glutamyltransferase [(gamma-glutamyl)-peptide:amino acid gamma-glutamyltransferase, EC 2.3.2.2] from human liver and compared some of its properties with the same enzyme prepared from human kidney. The enzymes from these two sources are very similar with respect to initial velocity kinetic constants, pH optima of the transpeptidation and autotransfer reactions, heat stability, competitive inhibition by glutathione of the colorimetric assay in which gamma-glutamyl-4-nitroanilide is substrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 22 publications
4
9
0
1
Order By: Relevance
“…Not surprisingly, the hepatic GGT associated with the bile ductular cell hyperplasia possessed catalytic properties which were very similar to those demonstrated for the GGTs of normal rat and human kidney (34)(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Not surprisingly, the hepatic GGT associated with the bile ductular cell hyperplasia possessed catalytic properties which were very similar to those demonstrated for the GGTs of normal rat and human kidney (34)(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 61%
“…The bile ductular epithelial cell isolate was prepared by first mincing the tissue fragments in 50 ml Leibowitz L-15 tissue culture medium, pH 7.4, supplemented with 1 gm per liter bovine serum albumin, 36 mM HEPES, 8.3 mM a-D(+)-ghcose, 0.1 FM insulin, 2 mM L-glutamine, 3% fetal calf serum, 100,000 units per liter penicillin G and 100 mg per liter streptomycin sulfate. To this was added 18,000 units collagenase, 35,000 units hyaluronidase, 6,500 units deoxyribonuclease I and 5 mg soybean trypsin inhibitor, and the mix was then vigorously shaken for 50 min at 37°C. The resulting cell suspension was cooled at 4°C and consecutively filtered through four Nitex Swiss nylon monofilament screens (TETKO, Elmford, NY) having mesh pore diameters of 253, 100, 60 and 20 pm, respectively.…”
Section: Isolation Of Hyperplastic Bile Ductular Tissue and A Bile Dumentioning
confidence: 99%
“…27 Datura stramonium agglutinin (DSA) has strong affinity for the GGT with a complex structure of saccharide, and low affinity for the GGT with a simple sugar chain. 28 Our laboratory successfully separated the isoenzyme of GGT using DSA-sepharose affinity chromatography, and clinical evaluation of DSA-GGT showed good specificity and sensitivity for the diagnosis of HCC. 19 Nevertheless, these measurements of the isoenzyme of GGT were based on electrophoresis or column chromatography, which were complicated, time-consuming and unsuitable for handling large numbers of serum samples.…”
Section: Discussionmentioning
confidence: 80%
“…Some data showed the isoenzyme of GGT with characteristics of a more complex structure of saccharide 27 . Datura stramonium agglutinin (DSA) has strong affinity for the GGT with a complex structure of saccharide, and low affinity for the GGT with a simple sugar chain 28 . Our laboratory successfully separated the isoenzyme of GGT using DSA‐sepharose affinity chromatography, and clinical evaluation of DSA‐GGT showed good specificity and sensitivity for the diagnosis of HCC 19 …”
Section: Discussionmentioning
confidence: 98%
“…In adult liver, GGT is localized in the biliary pole of hepatocytes and in cholangiocytes and hence secreted in bile [3] , [5] . Plasma GGT is supposed to origin from liver [6] , [7] and early studies demonstrated that it is associated with several carriers having different molecular weights, densities and charges [8] , [9] . Nevertheless, the mechanism of release, the structures and the clinical significance of such carriers have not been completely characterized.…”
Section: Introductionmentioning
confidence: 99%